Enhancing road construction management in Peru through virtual design and construction integration - Ariza Flores, Victor Andre (2024)
This study examines the integration of Building Information Modeling (BIM) with Project Production Management (PPM) and Integrated Concurrent Engineering (ICE) under the Virtual Design and Construction (VDC) framework to address chronic inefficiencies in road infrastructure projects in Peru. Focusing on a 93 km road project in Puno, the research demonstrates that the combined VDC approach leads to significant improvements in project management. Key findings include a 25% reduction in project delays and a 15% decrease in overall project costs compared to traditional management methods. The implementation of VDC also resulted in a 90% reduction in design conflicts and a 95% improvement in the resolution of construction observations. Production metrics were established, showing that BIM scope fulfillment reached 100%, and key stakeholders' attendance at ICE sessions exceeded85%, ensuring effective interdisciplinary coordination. The study highlights the critical role of coordinated BIM, PPM, and ICE processes in mitigating risks and enhancing project delivery in Peru. These results showthat adopting the VDC framework can lead to substantial efficiency gains in future road infrastructure projects. Recommendations include the establishment of continuous training programs and the creation of robust digital infrastructures to support the widespread adoption of VDC in the Peruvian construction sector.